Robocop : trilogy collection [videorecording (DVD)] - Bottin, Rob (2014)
Robocop: "Set in Detroit sometime in the near-future, the film is about a policeman killed in the line of duty, who the department decides to resurrect as a half-human, half-robot supercop. The robocop is indestructible, and within a matter of weeks he has removed crime from the streets of Detroit. However, his human side is tortured by his past, and he wants revenge on the thugs who killed him."--Stephen Thomas Erlewine, All Movie Guide.